Endocannabinoid-mediated regulation of depression in the ovBNST - Zhu, Riming; Li, Jie; Zhang, Xia; Zhang, Bin (Frontiers in Neuroscience, 2025)
IntroductionThe bed nucleus of stria terminalis (BNST) acts as a crucial hub for assessing vigilant threats, with the oval subnucleus (ovBNST) being enriched in endocannabinoid ligands and receptors. The endocannabinoid system (ECS) is well recognized for its role in stress responses. However, the molecular and circuitry mechanisms through which the ovBNST ECS mediates chronic stress induced depressive phenotypes remain unclear.Methods and resultsThe chronic unpredictable mild stress (CUMS) was optimized to model the depression-like behaviors and body weight loss in mice. By utilizing the endocannabinoid sensor, an increased release of endocannabinoid in the ovBNST was probed in response to acute stress. Local blockage of ovBNST cannabinoid type 1 receptor (CB1R) with NESS0327 induced both anhedonia and despair depressive phenotypes in naïve mice. In contrast, intra-ovBNST infusion of either CB1R agonist or cannabinoid hydrolase inhibitor JZL-184 ameliorated despair-like behaviors while merely changed anhedonia in CUMS mice. By combining viral tracing with RNAscope and western blotting, the reduction in CB1R transcriptional and translational level was found to be associated with the CUMS induced depressive disorders. This reduction may be attributed to the changes in ovBNST located presynaptic CB1R that originates from the medial prefrontal cortex (mPFC).DiscussionOverall, these results suggest that chronic stress may restructure the ovBNST ECS to result in depressive phenotypes. This study may extend the comprehension of ECS in the ovBNST, specifically its role in modulating the pathogenesis of depressive disorders induced by chronic stress.